2009
DOI: 10.1243/09544070jauto1114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the NOx emissions from heavy-duty diesel engines with the addition of cetane improvers

Abstract: The exhaust emissions from heavy-duty diesel engines (HDDEs) contribute to the degradation of ambient air quality; therefore, environmental agencies have created stringent emissions standards. Since the implementation of these standards, overall engine and fuel technology improvements have created a significant reduction in emissions. This study was completed in order to evaluate oxides of nitrogen (NO x ) emissions from fuels with and without cetane-improving additives in recent and early production electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…They showed that these additives can reduce NO x emission increases to some extent, however, the magnitude of the reductions was dependent on the base fuel aromatic content [39]. Several other authors have tested DTBP and 2-EHN additives and observed some potential for mitigating NO x increases with biodiesel blends [40][41][42][43][44][45]. The effect of cetane improvers tends to be less or negligible in newer engine technologies [2,40].…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that these additives can reduce NO x emission increases to some extent, however, the magnitude of the reductions was dependent on the base fuel aromatic content [39]. Several other authors have tested DTBP and 2-EHN additives and observed some potential for mitigating NO x increases with biodiesel blends [40][41][42][43][44][45]. The effect of cetane improvers tends to be less or negligible in newer engine technologies [2,40].…”
Section: B)mentioning
confidence: 99%
“…Several other authors have tested DTBP and 2-EHN additives and observed some potential for mitigating NO x increases with biodiesel blends [40][41][42][43][44][45]. The effect of cetane improvers tends to be less or negligible in newer engine technologies [2,40]. The results of a study performed by Durbin et al were mixed for different additives tested on a different 2006 Cummins ISM engine, with a 1% DTBP additive blend showing NO x neutrality for B20 and lower blends, while other tests using an 2-EHN additive blend were not successful at mitigating NO x emissions even at blend levels as low as 5% [10,11].…”
Section: B)mentioning
confidence: 99%
“…It is noted that the reduction of NO X at low engine loads is most probably related to the fact that biodiesel naturally has a higher cetane number than ULSD. With the use of a cetane improver in the B20 blend only a small increase in NO X is seen over the baseline ULSD [12].…”
Section: Emissions As a Function Of Fuel Propertiesmentioning
confidence: 93%
“…A study of cetane improvers in ULSD and biodiesel fuels was conducted at West Virginia University to determine if the fuel additives could have any beneficial effects on combustion to reduce NO X emissions. The reduction of NO X with the use of biodiesel fuels is very compelling since one of the drawbacks to biodiesel fuel is the increased NO X emissions [12].…”
Section: Emissions As a Function Of Fuel Propertiesmentioning
confidence: 99%
See 1 more Smart Citation